Airportscape And Its Effects On Emotions And Satisfaction: The Moderating Roles Of Sense Of Place And Environmental Responsiveness - Yerimou, Pantelitsa; Themistocleous, Christos (My University, 2024)
This study delves into travellers' experiences, including an in-depth evaluation of both physical and human-related aspects that contribute to the airport environment. Specifically, the study investigates the impact of the airport environment on the emotions evoked, observing these emotional reactions and the environment as preceding factors to airport satisfaction. Notably, the study digs into the eTects of two key moderators, sense of place and environmental responsiveness, reviewing their significant impact in this academic context.
Keywords: Airport Atmospherics; Sense of place; Enviromental Psychology; Authenticity